Utilizing Corporate Social Responsibility to Strengthen Brand Equity - Dewi Indriani Jusuf (Neo Journal of economy and social humanities, 2023)
This research aims to analyze and evaluate the role of using Corporate Social Responsibility (CSR) in strengthening a company's brand equity. Utilizing CSR has become a major focus for companies that want to improve their brand image in the eyes of consumers and society. This research uses qualitative analysis methods with descriptive methods. The research results show that effective implementation of the Corporate Social Responsibility (CSR) program provides significant benefits in strengthening a company's brand equity. Active participation in CSR activities not only improves a company's reputation in the eyes of consumers, but also differentiates the brand from competitors, builds close relationships with consumers, and increases customer loyalty. In addition, engagement in CSR also helps companies manage reputational risks related to social and environmental issues, while ensuring compliance with relevant CSR regulations and standards. Thus, CSR has an important role in establishing a strong and responsible brand image, which ultimately supports a company's long-term growth and sustainability in a competitive market.